ANALYSIS COMPONENTS OF PHYSICAL CONDITION ON WATER SKI SPORTS FOR THE NUMBER OF PUSLATDA MEN SLALOM EAST JAVA - Imada, Hind Nada; Irawan, Roy Januardi (Jurnal Kesehatan Olahraga, 2019)
ABSTRACTANALYSIS COMPONENTS OF PHYSICAL CONDITION ON WATER SKI SPORTS FOR THE NUMBER OF PUSLATDA MEN SLALOM EAST JAVA Name                         : Hind Nada ImadaNIM                            : 14060484079Study Program            : Sports ScienceDepartment                 : Health and Recreation EducationFaculty                        : Sport ScienceName of Institution    : Surabaya State UniversityAdvisor                       : Roy Januardi Irawan, S.Or., M.Kes The slalom number is a sport that requires special physical conditions. To reach the achievement, an athlete must have good physical condition. The purpose of this study was to determine the needs of the physical condition components needed by the water sky branch of the number men slalom of Regional Training Center in East Java with 7 people.The type of research used is quantitative with a descriptive approach. Based on the analysis of data processing, obtained research data in the form of the results of the correlation of physical tests with slalom technical skills test of each athlete. From these calculations, the physical condition component of ankle flexibility test has a positive correlation with a value of 0.569. Abdominal muscle strength test occupies the second position with a correlation value of 0.405. The different results occur in the balance test which shows a correlation value of 0.194, hip flexibility test with a correlation value of 0.067, hand grip strength test with a correlation value of 0.055 and arm, shoulder and back muscle strength tests have a correlation value of -0.695 which means that there is no relationship on slalom technical skills. While balance, hip flexibility, leg muscle strength, hand grip strength, abdominal muscle strength and arm, shoulder and back muscle strength, arm and shoulder flexibility have no relationship to slalom skills.Thus it can be concluded that ankle flexibility, abdominal muscle strength is a major component of physical condition that is most needed and influences slalom athletes' technical skills. Keywords: Physical Conditions, Water Skiing, Slalom